A Generative Artificial Intelligence–Based Learning Resources for Computing Students in Tanzania Higher Learning Institutions - Mbembati, Hadija; Bakiri, Hussein (University of Dar es Salaam Library Journal, 2025)
Generative Artificial Intelligence (GenAI) is one of the emerging technologies that students utilise as a learning resource in their computer science courses. The GenAI tools, such as Chat Generative Pre-Trained Transformer (ChatGPT), assist students with learning tasks that are always available and on demand. However, the preferred GenAI learning resources in the context of awareness of different GenAI tools, their applicability in various learning tasks, and GenAI usage are unclear. Therefore, this paper investigates the preferred AI-based learning resources for computing students in Higher Learning Institutions (HLIs). The survey data were collected from 571 undergraduate students in three Tanzania HLIs. The results show that, despite the widespread use of GenAI learning resources, traditional learning resources continue to be employed in the learning process. The preferred learning resources differ depending on the tasks and the year of study. The study findings showed that computing students mostly use GenAI tools, such as ChatGPT and OpenAI, in various learning tasks. The findings offer valuable guidance for educators and policymakers on how to safely implement GenAI-based learning tools that effectively support students' learning needs in this GenAI era. https://dx.doi.org/10.4314/udslj.v20i1.9